2019
DOI: 10.2136/vzj2018.11.0205
|View full text |Cite
|
Sign up to set email alerts
|

Water Retention and Pore Size Distribution of a Biopolymeric‐Amended Loam Soil

Abstract: Core Ideas Transversal relaxation time spectra were a good proxy to determine pore size distribution. Chitosan provides more degradable C to the soil microbial community than Arabic gum. The water retention curve showed that 10 g Arabic gum kg−1 soil decreased plant‐available water. The same amount of chitosan increased available water content compared with the reference soil. The pore size distribution (PSD) of biopolymeric‐amended soils is rarely investigated due to difficulties in its quantification using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
1
1
0
Order By: Relevance
“…With the application of WAP, the unoccupied pore spaces are filled by WAP, which absorbs water (Figure 2a). Similar trends were discussed in the literature (Wei and Durian, 2013; Rahmati et al., 2019). With the application of WAP, the soil–polymer interaction takes place on the surface of soil particles, thereby enhancing the specific surface area, which helps to retain water in the form of thin films on the surface of the soil.…”
Section: Resultssupporting
confidence: 89%
“…With the application of WAP, the unoccupied pore spaces are filled by WAP, which absorbs water (Figure 2a). Similar trends were discussed in the literature (Wei and Durian, 2013; Rahmati et al., 2019). With the application of WAP, the soil–polymer interaction takes place on the surface of soil particles, thereby enhancing the specific surface area, which helps to retain water in the form of thin films on the surface of the soil.…”
Section: Resultssupporting
confidence: 89%
“…For example, Manzanal et al [24] reported an increase in the air entry value (AEV) from 300 kPa to 600 kPa for a highplasticity silt from Comodoro, Argentina, when 0.5% (dry mass basis) of anionic calcium lignosulfonate was used. Likewise, the water content has been reported to increase by 5% for a loamy soil from Maragheh, Iran [25], and by 100% for a sandy clay from Jumunjin, Korea [26], for 1% cationic chitosan and 0.75-1% anionic xanthan gum, respectively. The saturated hydraulic conductivity (k s ) was observed to decrease for a poorly graded sand from Songkhla, Thailand, by almost three orders of magnitude (from 6.9 × 10 −5 m/s to 2.3 × 10 −8 m/s) when 22.5% of anionic para rubber was used [27].…”
mentioning
confidence: 99%